Antibacterial and anti-biofilm activities of crude extracts of Lawsonia inermis against Methicillin Resistant Staphylococcus aureus - AG, Triveni; Mendem Suresh Kumar,; Shivannavar, Channapa T; Gaddad, Subhaschandra M (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Â  Objective: The continuous rise in the prevalence of multi drug resistance pathogens globally is threatening the treatment and management of infectious diseases. Ethno medicine plays a key role in the exploration for novel bioactive compounds. The present study evaluates the antibacterial and antibiofilm activities of the crude extracts of Lawsonia inermis against clinical isolates of methicillin resistant Staphylococcus aureus (MRSA). Materials and methods: Shade dried and finely powdered leaves of the plant were extracted by maceration method using six solvents methanol, acetone, ethyl acetate, chloroform, petroleum ether and n-hexane. Antibacterial and antibiofilm activities of the extracts against MDR MRSA by agar cup diffusion and tube method respectively. Results: Methanol extract showed the highest antibacterial activity of 18mm compared to other extracts. Similarly, petroleum ether extract showed highest biofilm inhibition of 84.7%. Other solvent extracts also exhibited significant biofilm inhibition [n-Hexane-83.6%, Ethyl acetate -79.5%, Chloroform-79.2%, Acetone -77% and Methanol-77%]. Conclusion: The leaf extracts of L. inermis have shown promising biofilm inhibitory activity and good antibacterial activity, which can be explored for the development of new drugs for the MDR pathogens. Â  Keywords: Antibioticacivity, Antibiofilm activity, L.inermis, MRSA